Do subterranean mammals use the Earth's magnetic field as a heading indicator to dig straight tunnels? - Malewski, Sandra; Begall, Sabine; Schleich, Cristian E; Antenucci, C Daniel; Burda, Hynek (PeerJ, 2018)
Subterranean rodents are able to dig long straight tunnels. Keeping the course of such "runways" is important in the context of optimal foraging strategies and natal or mating dispersal. These tunnels are built in the course of a long time, and in social species, by several animals. Although the ability to keep the course of digging has already been described in the 1950s, its proximate mechanism could still not be satisfactorily explained. Here, we analyzed the directional orientation of 68 burrow systems in five subterranean rodent species (Fukomys anselli, F. mechowii, Heliophobius argenteocinereus, Spalax galili, and Ctenomys talarum) on the base of detailed maps of burrow systems charted within the framework of other studies and provided to us. The directional orientation of the vast majority of all evaluated burrow systems on the individual level (94%) showed a significant deviation from a random distribution. The second order statistics (averaging mean vectors of all the studied burrow systems of a respective species) revealed significant deviations from random distribution with a prevalence of north-south (H. argenteocinereus), NNW-SSE (C. talarum), and NE-SW (Fukomys mole-rats) oriented tunnels. Burrow systems of S. galili were randomly oriented. We suggest that the Earth's magnetic field acts as a common heading indicator, facilitating to keep the course of digging. This study provides a field test and further evidence for magnetoreception and its biological meaning in subterranean mammals. Furthermore, it lays the foundation for future field experiments.
Keywords: Mole-rats; Subterranean rodents; Magnetoreception; Burrow systems; Orientation